KEKERABATAN BAHASA JAWA DAN BAHASA GAYO: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Muhammad Surip; Dwi Widayati (Jurnal Bahasa Lingua Scientia, 2019)
This study aims to reveal the kinship relationship of Javanese and Gayo languages ​​seen from some vocabulary similarities, as well as estimate the time separation with the run of error. The method used is descriptive qualitative and quantitative with the techniques refer to note. This research data is a vocabulary in BJ and BG obtained from various written sources and informant interview. From 200 words Swadesh to BJ and BG there are 13% ie 25 words pairs of relatives. These data provide evidence that BJ and BG are not close relatives because the core vocabulary equation is less than 36% or part of sub-grouping. But the language of both comes from the same pilum or stock. Both languages ​​have identical word pairs that are all similar phonemes of 16 relatives couples; 12 relatives couples have a phonemic correspondence; 9 relatives couples who are phonetically similar; and 13 relatives couples who have a different phoneme. The time of split of both languages ​​was 3,393 thousands of years ago. It is thought that this second language was a single language about 3.4 thousands years ago and is thought to have begun to separate from a proto language about the 5th century BC. It is estimated that the age of both languages ​​is a single language on 4,712 + 335 years ago and at 5,047+335 years ago.